On becoming a scholar : socialization and development in doctoral education - Gardner, Susan K. (Susan Kristina), 1974-; Mendoza, Pilar, 1974- (Stylus Pub., 2010)
Despite considerable research that has provided a better understanding of the challenges of doctoral education, it remains the case that only 57% of all doctoral students will complete their programs. This book comprehensively critiques existing models and views of doctoral student socialization; offers a new model that incorporates concepts of identity development, adult learning, and epistemological development; and concludes by developing practical recommendations for all stakeholders. The contributors bring the issues vividly to life by creating five student case studies that, throughout the book, progressively illustrate key stages and typical events of the socialization process. These fictional narratives crystallize how particular policies and practices can assist or impede the formation of future scholars.